Localization, cloning, and expression of genetic determinants for bacteriophage resistance (Hsp) from the conjugative plasmid pTR2030. - Hill, C (1989)
Genetic determinants for a bacteriophage resistance mechanism (Hsp+) encoded by plasmid pTR2030 (46.2 kilobases [kb]) were localized by mapping an 11.5-kb deletion that accompanied the transition of Lactococcus lactis LMA12-4 transconjugants (M. E. Sanders, P. J. Leonard, W. D. Sing, and T. R. Klaenhammer, Appl. Environ. Microbiol. 52:1001-1007, 1986) from phage resistance to phage sensitivity. The deleted 34.7-kb replicon (pTR2023, Hsp-) retained its conjugative ability, demonstrating that the phage resistance and conjugal transfer determinants were genetically distinct. The Hsp region of pTT2030, which was contained within a 13.6-kb BglII fragment, was cloned into the BamHI site of bacteriophage lambda EMBL3, and Hsp was subcloned into the Escherichia coli-Streptococcus shuttle vector pSA3. The recombinant plasmids pTK6 and pTK9 were recovered in E. coli HB101 and contained a 13.6-kb insert in opposite orientations. L. Lactis MG1363 transformants carrying pTK6 or pTK9 exhibited a significant reduction in plaque size, in addition to a slight reduction in the efficiency of plaquing for both prolate and small isometric phages. Phenotypic reactions observed for the recombinant plasmids suggest that pTR2030-encoded Hsp acts similarly against both prolate and small isometric phages. Tn5 mutagenesis was used to define the region essential for the expression of the Hsp+ phenotype. Any of four insertions within a 3-kb region resulted in the loss of phage resistance, whereas a further 26 insertions outside this locus had no effect on Hsp expression. In vitro deletion analysis confirmed that the 3-kb region contained all the information necessary for the observed resistance.